INNOVATIVE EXPLORATION ON EMPOWERING STUDENTS TO STUDY AND PROPAGANDIZE THE NEW THOUGHT UNDER THE INTERNET THINKING TAKING XI JINPING THOUGHT ON THE SOCIALISM WITH CHINESE CHARACTERISTICS IN A NEW ERA AS AN EXAMPLE - Ling, Huang (PEOPLE: International Journal of Social Sciences, 2019)
The number of Chinese citizens has reached 802 million until June, 2018, which indicates that the Internet thinking is becoming the mainstream thinking way and the cyberspace has been the important platform for students’ ideological education, daily management work and publicity work. Based on its characteristics, the paper, following the Internet thinking, will discuss the innovative methods to conduct ideological education in universities and colleges. This paper will start from three aspects: user thinking, creating a learning environment with college students as its main body, product thinking, laying great emphasis on the needs of college students and communication thinking, seizing the communication features of the Internet era and put forward the innovative modes and their advantages of empowering students to study and propagandize the New Thought in a new era under the Internet thinking. This will leave the path clear for further researching and utilizing the Internet thinking and securing the high efficiency in ideological education work. The relevant research in this paper is of practical significance and reference value for colleges and universities to make forward students’ ideological education and theoretical learning.